2017
DOI: 10.1136/jramc-2017-000791
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Alternative Healthy Eating Index (AHEI-2010) with depression, stress and anxiety among Iranian military personnel

Abstract: An inverse association between adherence to the AHEI-2010 and odds of depression and anxiety was found. Further studies are required to clarify this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 28 publications
0
42
1
2
Order By: Relevance
“…Two emerging research priority areas that were identified in the 4th ICSPP survey were sleep and nutrition. Sleep 19,20 and nutrition 21,22 have also been identified as priority areas in other publications, which shows an increased focus on lifestyle factors as a means to optimizing health and performance in military populations. Retired U.S. Army Surgeon General, LTG Patricia Horoho initiated a major public health campaign in 2012 named the Performance Triad, that championed the importance of activity, nutrition, and sleep as major contributors to Soldiers' overall health, performance, and resiliency.…”
Section: Discussionmentioning
confidence: 99%
“…Two emerging research priority areas that were identified in the 4th ICSPP survey were sleep and nutrition. Sleep 19,20 and nutrition 21,22 have also been identified as priority areas in other publications, which shows an increased focus on lifestyle factors as a means to optimizing health and performance in military populations. Retired U.S. Army Surgeon General, LTG Patricia Horoho initiated a major public health campaign in 2012 named the Performance Triad, that championed the importance of activity, nutrition, and sleep as major contributors to Soldiers' overall health, performance, and resiliency.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining studies were carried out in Europe including Belgium (n = 6, 7%) [22,[70][71][72][73], Finland (n = 3, 3%) [21,34], the United Kingdom (n = 3, 3%) [28,45,48], Norway (n = 3, 3%) [62,94,96], Italy (n = 1, 1%) [31], Greece [23], and France (n = 1, 1%) [50]. Asia included studies in Israel (n = 4, 4%) [2,47,56,81], Iran (n = 2, 2%) [76,90] Malaysia (n = 1, 1%) [57], and Japan (n = 1, 1%) [61]. Two studies were undertaken in Australia (2%) [44,96].…”
Section: Study Locationmentioning
confidence: 99%
“…One study did not report on participant numbers [45]. Forty-five of the 89 studies included male personnel (51%) [ The military population most frequently studied, in descending order, was the army with n = 48 (54%) [2,6,7,[21][22][23][24][29][30][31][32]34,35,[37][38][39][40][43][44][45][46][47][48][50][51][52][53][56][57][58][59][60][61][62]66,[70][71][72][73]76,77,82,84,88,89], followed by veterans n = 18 (20%) [20,[90][91]…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations